Psychological Features of Students' Anxiety During their First Year at University - T M Babaev; N V Kargina (Peoples' Friendship University of Russia (RUDN University), 2014)
The purpose of this article is to highlight the problems of freshmen's adaptation during their transition period from a high school to university. The urgency of this problem is that without the proper adaptation to new educational conditions the yesterday high-school students can develop several serious health problems, such as high neuroticism and anxiety.